The intensity of transpiration of trees in period of drought in different ecological zones of Khmelnytskyi - Ганаба, Д. В. (Scientific Progress & Innovations, 2016)
One of the important factors of influencing on the operation of physiological processes and optimize the productivity of trees is the water regime. In the article we analyzed the intensity of transpiration of trees in conditions of unfavorable factors of natural and anthropogenic origin. The results showed the difference between the levels of water evaporation in the leaves of trees growing in the park area and along the streets of Khmelnytskiy. Aesculus hippocastanum, Acer platanoides are the most vulnerable to drought and adverse factors of natural and anthropogenic loads. Рісеа abies, Populus pyramidalis Roz, Tilia cordata are the most resistant plants.